2019
DOI: 10.1371/journal.pbio.3000319
|View full text |Cite
|
Sign up to set email alerts
|

Social intolerance is a consequence, not a cause, of dispersal in spiders

Abstract: From invertebrates to vertebrates, a wealth of species display transient sociality during their life cycle. Investigating the causes of dispersal in temporary associations is important to better understand population dynamics. It is also essential to identify possible mechanisms involved in the evolutionary transition from transient to stable sociality, which has been documented repeatedly across taxa and typically requires the suppression of dispersal. In many animals, the onset of dispersal during ontogeny c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…We know little about the mechanisms that underlie kin recognition in spiders, but behavioural studies indicate that it is mediated by chemical cues. This is supported by the detection of family-specific cuticular chemical profiles in spiderlings of both subsocial and solitary species [33,34]. Cuticular chemical profiles of A. bruennichi are complex in both males and females, including diverse hydrocarbons and large amounts of unusual long-chained esters, so-called wax esters (WEs) ( [35], this study).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…We know little about the mechanisms that underlie kin recognition in spiders, but behavioural studies indicate that it is mediated by chemical cues. This is supported by the detection of family-specific cuticular chemical profiles in spiderlings of both subsocial and solitary species [33,34]. Cuticular chemical profiles of A. bruennichi are complex in both males and females, including diverse hydrocarbons and large amounts of unusual long-chained esters, so-called wax esters (WEs) ( [35], this study).…”
Section: Introductionmentioning
confidence: 63%
“…Learning templates from other individuals is only reliable when the risk of erroneously sampling unrelated individuals is low and when phenotypes do not change over time. Family-specific cuticular profiles in spiderlings have been found in both subsocial and solitary spiders [33,34], and kin recognition occurs during the gregarious phase in some species [18][19][20][21]. However, in the subsocial Stegodyphus lineatus (Eresidae), chemical profiles of spiderlings change markedly at the onset of dispersal from the egg-sac [33], suggesting that template formation from siblings during the gregarious phase after hatching may not be practical for kin discrimination as adults.…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that brown recluse spiders do disperse from preferred habitat into unsuitable habitat, presumably, in a search of new areas to colonize. The preponderance of immature brown recluse spiders and the correlation of emigrants with higher populations in the garage offers some support for this conclusion (though see Chiara et al 2019). The fact that all adults captured were male is consistent with the generally higher activity and longer movements of males recorded in many species, including brown recluse spiders (Cramer & Hileman 2018).…”
mentioning
confidence: 63%
“…In theory, spiders may also form stable groups when there is an unlimited energy supply ( Figure 6 ). However, a recent study has emphasized the importance of social interaction in the route to permanent sociality, and found that reduction in the level of starvation failed to repress the aggressiveness triggered by social isolation ( Chiara et al, 2019 ). Another study denoted that underfed colonies dispersed significantly earlier than colonies fed without restriction ( Krafft et al, 1986 ).…”
Section: Discussionmentioning
confidence: 99%